On the genus Tetartopeus Czwalina, 1888 of Turkey. A new species and additional records (Coleoptera: Staphylinidae: Paederinae) - Anlaş Si̇nan (Zootaxa, 2009)
Tetartopeus tezcani sp. n. from Anatolia, Turkey, is described, illustrated and distinguished from related congeners. Tetartopeus persicus Coiffait is reported from Turkey for the first time. A key to the Turkish species of Tetartopeus is presented.